ANALISIS PENGARUH TEKNOLOGI KECERDASAN BUATAN TERHADAP PENYEBARAN BERITA HOAX DI MEDIA SOSIAL - Renaldi, Alfin; Imayan, Rifki; Muda, Mas; Razzaq, Abdur (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
In this article, a comprehensive review of literature from 25 sources spanning the years 2020–2025 is used to study the impact of artificial intelligence (AI) technology on the spread of fake news on social media. AI algorithms on platforms like Facebook and Twitter prioritize emotional content, causing fake news to spread 6 times faster than real news, according to qualitative content analysis. Automated chatbots were responsible for 40% of hoax comments in the 2016 US and 2024 Indonesian election disinformation campaigns, while AI-based deepfake technology produced manipulative videos that convinced 78% of users. 61% of viral hoax trends on Twitter originated from AI bots with a Botometer score of over 0.7. If used as a "disinformation production machine," digital democracy is in great danger. According to research, algorithm transparency, hybrid AI-human truth testing, and national digital literacy must be regulated in accordance with the revised 2025 ITE Law